Mental disorders and long‐term labour market outcomes: nationwide cohort study of 2 055 720 individuals. (26th August 2019) - Hakulinen, C.; Elovainio, M.; Arffman, M.; Lumme, S.; Pirkola, S.; Keskimäki, I.; Manderbacka, K.; Böckerman, P.
Abstract : Objective: To examine the associations between an onset of serious mental disorders before the age of 25 with subsequent employment, income and education outcomes. Methods: Nationwide cohort study including individuals ( n = 2 055 720) living in Finland between 1988–2015, who were alive at the end of the year they turned 25. Mental disorder diagnosis between ages 15 and 25 was used as the exposure. The level of education, employment status, annual wage or self‐employment earnings, and annual total income between ages 25 and 52 (measurement years 1988–2015) were used as the outcomes. Results: All serious mental disorders were associated with increased risk of not being employed and not having any secondary or higher education between ages 25 and 52. The earnings for individuals with serious mental disorders were considerably low, and the annual median total income remained rather stable between ages 25 and 52 for most of the mental disorder groups. Conclusions: Serious mental disorders are associated with low employment rates and poor educational outcomes, leading to a substantial loss of total earnings over the life course.